Anomalous aortic origin of coronary arteries: is the unroofing procedure always appropriate?. (9th November 2020) - Mostefa Kara, Meriem; Fournier, Emmanuelle; Cohen, Sarah; Hascoet, Sebastien; Van Aerschot, Isabelle; Roussin, Regine; El Zoghbi, Joy; Belli, Emre
Abstract: OBJECTIVES: Anomalous aortic origin of the coronary artery (AAOCA) with an interarterial ± an intramural course is a rare anomaly that carries a high risk of ischaemic events and even sudden death. The unroofing of the intramural course has been adopted as the gold standard surgical treatment. However, some anatomical forms need alternative techniques. METHODS: We reviewed the surgical cohort with AAOCA managed at our institution between 2005 and 2019 and analysed the anatomical and clinical outcomes. RESULTS: Thirty-nine patients underwent surgical interventions. The median age was 14 years (10–26 years). Twenty-eight patients (72%) had right AAOCA, and 11 (28%) had left AAOCA. Thirty-one (80%) patients presented with symptoms. The symptoms were chest pain in 22 patients (56%), syncope in 5 patients (13%), cardiac arrest during exercise in 2 patients (5%), dyspnoea in 6 patients (15%) and dizziness in 13 patients (33%). An ischaemic test was performed in 32 patients: Only 4 patients (10%) had positive results from the ischaemic test. All patients had computed tomography angiography scans to confirm the precise anatomical features of the anomaly. Repair techniques included 30 unroofing procedures (77%) with an associated translocation of the pulmonary artery for 11 patients in our early experience. In 6 patients the unroofing procedure was not feasible because of the absence of an intramural distinct segment or was judged intraoperatively not appropriate. A reimplantation of the anomalous coronary artery was performed in 2 patients (5%); 3 patients had coronary artery bypass grafting procedures (7%); and 3 (8%) had an isolated translocation of the pulmonary artery. There were no early or late deaths. All patients were free of symptoms. Computed tomography angiography scans performed in 31 cases showed a patent, non-restrictive coronary artery ostium. Seventeen patients underwent postoperative ischaemia testing and showed no evidence of ischaemia. CONCLUSIONS: Surgical correction in AAOCA is mandatory both for symptomatic and for asymptomatic patients with evidence of myocardial ischaemia under stress or with a restricted coronary artery segment. Surgical unroofing remains the gold standard but is not appropriate for all forms: alternative techniques should be considered. Surgical results are promising.